(untitled) (Alternautas, 2022)
This is part of the of Black Awareness Day and the Zumbi dos Palmares celebrations, at the José Bonifácio Cultural Centre in the city of Rio de Janeiro, where the first Kilunge Afro-Brazilian Book Fair was held on November 17th and 18th 1997. In addition to the launch of several new titles by Afro-descendant authors, or books specifically on the black issue, the poet Elisa Lucinda also participated in the event, and she presented her show entitled “The Similar”. Professor Milton Santos also gave a lecture at the event, in which he addressed contemporary issues of organisation and progress for the Afro-Brazilian community.